(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2014)
The cyclostationary based spectrum sensing algorithm is especially suitable for detection of orthogonal frequency division multiplexing (OFDM) signals that exhibit strong periodic correlation due to insertion of cyclic prefix between OFDM blocks.Normally, the cyclic prefix is used to remove the Intersymbol interference (ISI) and intercarrier interference (ICI) of the OFDM signal and so it eliminates a need for complex equalizer. In this paper, simulation results demonstrate the normalized spectrum correlation function of the primary OFDM signal used in cognitive radio systems with different values of cyclic frequency. Two techniques are assumed to be used as PAPR reduction of OFDM transmitted signal. The results show that only one of them has no apparent effect on the correlation performance of the cyclostationary detector. Finally, it is found that a reduction of 30% in the implementation complexity can be taken by suitable choice of detector cyclic frequency.